2003
DOI: 10.1055/s-2003-40107
|View full text |Cite
|
Sign up to set email alerts
|

Pylephlebitis mit Luft im Pfortadersystem

Abstract: In the differential diagnosis of sepsis, especially in combination with abdominal pain or gas in the portal venous system, pylephlebitis should be taken into account. Because of the high mortality, immediate further diagnostic testing and appropriate therapy of this rare diagnosis are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, the presence of portal venous gas (PVG) associated with PVT could be a rare but serious, even catastrophic condition in IBD patients [33]; to date 21 cases of PVG associated with CD have been reported in the scientific literature [3437]. Among 182 case studies reported by Chande et al [38], patients with UC or CD comprised 4% of the total.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of portal venous gas (PVG) associated with PVT could be a rare but serious, even catastrophic condition in IBD patients [33]; to date 21 cases of PVG associated with CD have been reported in the scientific literature [3437]. Among 182 case studies reported by Chande et al [38], patients with UC or CD comprised 4% of the total.…”
Section: Discussionmentioning
confidence: 99%
“…The CT scan findings in our patients were gas and clot in the affected vein. The finding of gas formation in the portal vein on CT scan has been implicated in pylephlebitis, but the diagnosis is not proven 12 . Ultrasound with Doppler helps in identifying flow abnormalities and also assesses the progression or resolution of thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of gas formation in the portal vein on CT scan has been implicated in pylephlebitis, but the diagnosis is not proven. 12 Ultrasound with Doppler helps in identifying flow abnormalities and also assesses the progression or resolution of thrombus. Magnetic resonance imaging is used to differentiate between acute and chronic thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually secondary to the development of intra-abdominal infective foci typically complicating diverticular disease, appendicitis and necrotizing pancreatitis [2] . This critical clinical condition can arise in inflammatory bowel diseases too [2] , [3] , [4] , [5] , [6] , [7] , [8] . However, in Crohn’s disease it is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Pylephlebitis was described as a Crohn’s disease complication in 1946 by Taylor [3] and, to the best of our knowledge, only other 8 cases have been reported so far [2] , [4] , [5] , [6] , [7] , [8] . Furthermore, only in three of them the superior mesenteric vein was described to be primarily involved.…”
Section: Introductionmentioning
confidence: 94%